Estudo da influência da camada de engobe sobre a curvatura central de revestimentos cerâmicos - Gennari, Ronaldo Crosio (Universidade Federal de São Carlos, 2011)
Given the importance of planarity of the tiles for covering of floor and walls, this work aims to identify the influence of engobe layer on the behavior of central curvature, and from then on, allowing a greater understanding of the phenomenon of coupling support-engobe-enamel. The engobes are currently used as intermediate layer of ceramic tiles. Among the functions provided by engobes, some can be highlighted, hide the color of the ceramic, eliminate surface defects, to prevent reactions between the substrate and the ceramic glaze. In addition, the engobe also have a role in the coupling between substrate and enamel, but this is one of the least studied in the literature. To conduct the study, distinct engobes compositions were formulated, with planned variations in their behavior during the burning (fusibility and thermal expansion). With the help of the technique of design of experiments (DOE) with 2k factorial analysis, it was possible to study the effect of these variables on the central curvature. Results helped to understand the effect of each variable and the role of engobe on the flatness of the ceramic tiles. From the analysis of the results obtained it was suggested a statistical method that can help reduce the central curvature of the tiles from the knowledge of the characteristics of the engobe to the same type of enamel.
Study of the influence of engobe layer on the central curvature of ceramic tiles
Keywords: Revestimentos cerâmicos; Planaridade; Cerâmica; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA